Doppler echocardiographic features of coronary arteriovenous fistula. Complementary roles of cross sectional echocardiography and the Doppler technique. Issue 5 (May 1984) - Miyatake, K; Okamoto, M; Kinoshita, N; Fusejima, K; Sakakibara, H; Nimura, Y
Abstract : The Doppler echocardiographic features of coronary arteriovenous fistula were investigated in eight patients with left or right coronary arteriovenous fistulas who had a continuous heart murmur in the upper precordial area and whose diagnoses were confirmed by coronary angiography. In four patients the dilated lumen of the coronary arteriovenous fistula was visualised by cross sectional echocardiography. Of these, three showed abnormal unidirectional continuous flow signals with broad velocity spectra in the fistula. Abnormal, powerful, unidirectional or bidirectional continuous Doppler signals were detected in part of the pulmonary artery in two of the eight patients, in part of the right ventricle in two, and in part of the right atrium in one; these signals were interpreted as indicating shunt flow. Although the opening of the fistula was difficult to visualise by cross sectional echocardiography, the pulsed Doppler technique helped identify the site in patients with dilatation of the coronary artery. In the remaining three patients with a small shunt no abnormal findings were obtained with cross sectional echocardiography or the Doppler technique. The size of the fistula below which no abnormal findings may be obtained by Doppler echocardiography still needs to be determined.